Developing Workers’ Performance and Its Role in Settling Financial Claim: An applied research in the General Iraqi Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research seeks to identify the dimensions of the development of staff performance (training ', incentives, management skills) and its impact on the settlement of compensatory claims adopted in the current research in the Iraqi insurance company،This research aims to highlight the role of developing insurance company’s workers’ performance in settling insurance compensation, and to check this process, the research was applied in the general Iraqi insurance company as it considered as the research community, and a sample was taken from this community that represented by company’s insurance department workers or by collecting actual data that is related to the research’s sample, in addition to the financial compensation data.The procedure used a questionnaire that included a set of items that helps to support the data that have been analyzed by statistical toolkits (repetition, percentage arithmetic mean standard deviation z test t test) were the researcher has concluded a group of conclusions, and the most important one was: Developing Iraqi insurance company's workers, performance has a vital role to upgrade worker's efficiency that reflects on settling compensation claims, which are important procedures in the company’s work and its relation with customers (the insured).